Association Between Insomnia and Migraine Risk: A Case–Control and Bidirectional Mendelian Randomization Study - Chu S; Wu Z; Wu Z; Wu J; Qian Y (Dove Medical Press, 2021)
Shujuan Chu,1 Zhilin Wu,1 Zhouyang Wu,1 Jing Wu,1 Yue Qian2 1Department of Anesthesiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People's Republic of China; 2Department of Dermatology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People's Republic of ChinaCorrespondence: Jing Wu; Yue Qian Email tounj_002@163.com; qianyue011@sohu.comBackground: The causal relationship between insomnia and migraine is contradictory and no study has been carried out among the Chinese population to date.Methods: In this case, we conducted a case-control study and a bidirectional mendelian randomization (MR) analysis to determine whether insomnia is causally related to the development of migraine. The instrumental variables for insomnia were derived from the largest genome-wide association study of 1,331,010 participants, while the genetic instruments for migraine were available from the largest meta-analysis of migraine with 59,674 cases and 316,078 controls.Results: In case-control study, subjects with insomnia have significantly higher risk of migraine (OR=4.29, 95% CI: 3.21- 5.74, P< 0.001), compared with those without insomnia. The bidirectional two-sample MR analysis revealed that insomnia was significantly associated with higher risk of migraine (OR=1.24, 95% CI: 1.11- 1.38, P=1.01× 10-4), and the results were validated in the UK Biobank data. The results showed no indication for directional pleiotropy effects as assessed by the MR-Egger intercept (P> 0.05).Conclusion: Conclusively, our study highlighted that increased migraine risk was confined to subjects with a genetic pre-disposition to insomnia, and these findings had potential implications for improving the sleep quality to reduce the burden of migraine.Keywords: mendelian randomization, insomnia, migraine, case-control